2015
DOI: 10.21863/jem/2015.4.2.007
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Entrepreneurial Leadership Style on Business Performance of Female owned SMEs in Dar es salaam, Tanzania

Abstract: This study attempts to determine the relationship between Entrepreneurial Leadership style and business performance of Small and Medium Enterprises (SMEs) owned or led by female CEOs in Dar es salaam, Tanzania. The research is based on secondary data from One World Action and Financial Sector Development Trust (FSDT) baseline survey databases, covering Kinondoni, Ilala and Temeke municipalities. Data cleaning was conducted using Roy (2010)s seven step methodology and analyzed quantitatively using Pearson Produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…It should be noted the dearth of research on entrepreneurial leadership and performance means that this area should be the focus of future inquiry (Renko et al, 2014(Renko et al, , 2015Huang et al, 2014;Arham et al, 2013). A review of the literature confirms the beneficial effect of TQM practices (Panuwatwanich & Nguyen, 2017, Qasrawi et al, 2017Costantini & Zanin, 2015) and entrepreneurial leadership (De Greef, 2014, Mgeni, 2015, Arham et al, 2013 on organizational performance. Surprisingly, very few studies have examined the combined impact of entrepreneurial leadership and TQM practices on the organizational performance of SMEs.…”
Section: Entrepreneurial Leadership Tqm Practices and Organizationamentioning
confidence: 90%
See 2 more Smart Citations
“…It should be noted the dearth of research on entrepreneurial leadership and performance means that this area should be the focus of future inquiry (Renko et al, 2014(Renko et al, , 2015Huang et al, 2014;Arham et al, 2013). A review of the literature confirms the beneficial effect of TQM practices (Panuwatwanich & Nguyen, 2017, Qasrawi et al, 2017Costantini & Zanin, 2015) and entrepreneurial leadership (De Greef, 2014, Mgeni, 2015, Arham et al, 2013 on organizational performance. Surprisingly, very few studies have examined the combined impact of entrepreneurial leadership and TQM practices on the organizational performance of SMEs.…”
Section: Entrepreneurial Leadership Tqm Practices and Organizationamentioning
confidence: 90%
“…The researchers found that there is a positive link between entrepreneurial leadership and organizational performance. Mgeni (2015) demonstrated that entrepreneurial leadership style is directly related to the organizational performance of Tanzanian SMEs. They concluded that the underperformance of Tanzanian SMEs is most likely due to the absence of entrepreneurial leadership skills.…”
Section: Entrepreneurial Leadership and Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data, the priority of activity program for SMEs is by developing Agroindustry as much as 671,058 units of SMEs, standardization of product for SMEs, and making 5 smelter consisting of 2 Foreign Investment and 3 Domestic Investment. Generally, SMEs is very difficult to be a big business (Zheltoukhova & Suckley, 2014;Mgeni, 2015;Mgeni & Nayak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The growing number of small and medium-sized business units will certainly be able to open large employment opportunities. However, this small business is still seen as a weak business performance ( Van der Vaart & Gibson, 2008;Mgeni, 2015;Mgeni & Nayak, 2015).…”
Section: Introductionmentioning
confidence: 99%